2-3(x-5)=4(x-1)

Simple and best practice solution for 2-3(x-5)=4(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-3(x-5)=4(x-1) equation:


Simplifying
2 + -3(x + -5) = 4(x + -1)

Reorder the terms:
2 + -3(-5 + x) = 4(x + -1)
2 + (-5 * -3 + x * -3) = 4(x + -1)
2 + (15 + -3x) = 4(x + -1)

Combine like terms: 2 + 15 = 17
17 + -3x = 4(x + -1)

Reorder the terms:
17 + -3x = 4(-1 + x)
17 + -3x = (-1 * 4 + x * 4)
17 + -3x = (-4 + 4x)

Solving
17 + -3x = -4 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
17 + -3x + -4x = -4 + 4x + -4x

Combine like terms: -3x + -4x = -7x
17 + -7x = -4 + 4x + -4x

Combine like terms: 4x + -4x = 0
17 + -7x = -4 + 0
17 + -7x = -4

Add '-17' to each side of the equation.
17 + -17 + -7x = -4 + -17

Combine like terms: 17 + -17 = 0
0 + -7x = -4 + -17
-7x = -4 + -17

Combine like terms: -4 + -17 = -21
-7x = -21

Divide each side by '-7'.
x = 3

Simplifying
x = 3

See similar equations:

| =(5x+18)(x-3) | | t^2+x^2=14 | | 3x+31=5x-27 | | -7x^2=175 | | -8x-(-3)+(-6)=4-x | | 3y-4(y-2)=10 | | 6(j+35)=132 | | 9t-9+18T=6T+12 | | -1+19m=11m+23 | | lnx=.33 | | 5-2p=-3p-5 | | .75a+4=.25(3a-16) | | 0.7(3x+4)=1.1-(x+2) | | 4(9d+2)=2(d-17)-8d | | 0.2(x+10)+0.2x=6 | | 7y=2y+10-15 | | [21-5x]=33 | | -2(5s-6)-12=-29(8s+8)-3 | | 5y-4=2y+20 | | 2z+4=5z | | 2+5(2+5)= | | 5x=12-32+x | | 4+9lnx=7 | | 7n-4=n+1 | | 3s+5(s+7)=99 | | x^2+8x+16=99 | | 114-d=83 | | 2*16= | | -4.6b=28.106 | | x-2x+20=12 | | -3=-6t-3 | | Y=20-6x |

Equations solver categories